(untitled) (مجلة إحالات, 2025)
لعلّ الملاحظ على التناّول النّحوي الدّراسات اللّسانيّة الترّاثية،الانشغال بوظيفة العناصر اللّسانيّة،ولكنّها قد اقتصرت على العناصر المورفولوجيّة منها خاصّة دون غيرها،وقد راعت فيها الوظيفة النّسق في مستواها الأفقي،الّذي يشتغل بالترّكيب اللّساني للعناصر،ومنها إلى وظيفة المعنى وما يكتنف من دوائره الدّلاليّة،في مستوى الشّاقول،الّذي يهتمّ بدلالات التّراكيب اللّسانيّة.فلم يبرح هذا التّناول الكلاسيكي رؤيته لوظيفة هاته العناصر ودلالاتها،ولم تتعدّى ذلك إلى ما يتجزأ عن تلك العناصر المورفيميّة،إلى ما تقلّ عنها من نظيراتها الفونيميّة؛فقد تقع في تفسير كثير من المضان النّحويّة الشّائكة،بالنّظر إلى المقاربة الفيزيائيّة الكمّيّة الّتي تكون أداةً لسانيّة إجرائيّة،تقوم على الغوص في أدقّ موطن وألطفه للعلاقة القائمة بين الوظيفة النّحويّة ودلالاتها،فيكون تفسيرها للظواهر اللّسانيّة،بما فيها المباحث النّحويّة أكثر عمقاً،وأدقّ تحليلاً،وأسلم تخريجاً،وأقرب إلى العلميّة،وأبعد عن النّسبيّة،الّتي رانت على التّخريجات الكلاسيكيّة،وتخطو بالدّرس اللّساني الحديث- منه العربي-خطوة عظيمة،نحو العلوم الدّقيقة،وتكون نتائجها أقرب إلى سلامة المنطق الرياضي، فيطمأن لها ويُترضى بها. The observation which is noted on the grammatical study in the traditional linguistic studies, concern of the function of the linguistic elements, but it was limited in particular to its morphological elements without others, it took into account the coherent function at its horizontal level, which operates with the linguistic structure of the elements, and of these at the function of meaning and its semantic circles, at the vertical level, which is interested in the meaning of linguistic structures. This classical approach has preserved his vision of the function of these elements and their implications, and has not gone beyond what is separate from these morphological elements, this may be in the interpretation of a lot of grammatical fluorescence, taking into account the quantitative physical approach, which is a procedural linguistic tool, based on a more in-depth and pleasant exploration of the relationship between grammatical function and its semantics, so that its interpretation of linguistic phenomena, including grammatical research, is more profound , more precise and more precise, closer to the scientist and far from the relativity, which was invented by classical interpretations, and takes general linguistics - from Arabic linguistics - a big step towards exact science, and its results are closer of the solidity of mathematical logic, so he reassures them and is satisfied with it.